3E analyses of battery-assisted photovoltaic-fuel cell energy system: Step towards green community. (December 2022) - Khan, Tahir; Waseem, Muhammad; Muqeet, Hafiz Abdul; Hussain, Muhammad Majid; Yu, Miao; Annuk, Andres
Abstract: Diesel generator-based energy systems (DGES) are often utilized for rural electrification, which is neither economical nor an eco-friendly choice. Also, fuel logistics in rural areas and uncertain varying prices of diesel are obstacles that make the DGES technically and economically unfeasible. Thus, a battery-assisted photovoltaic-fuel cell (PV-FC) green energy system (GES) is proposed to meet the energy demand of the rural community in Pakistan. 3E (energy, economic, and environmental) analyses are conducted to access the feasibility of GES in all three domains. The sensitivity analyses are performed to evaluate the effect of the most uncertain parameters on the economy of GES. In addition, the proposed GES is contrasted with DGES. It is investigated that the TNPC and COE of the proposed GES are 15% and 38.4% less expensive than DGES. The proposed GES contributes no emissions to the environment saving 384.47 tons/yr of greenhouse gas emissions as compared to DGES. Furthermore, no significant difference in the technical performance of both DGES and GES is observed. Hence, it is concluded that the proposed GES is financially, technically, and environmentally a feasible solution for rural electrification. Finally, future work is recommended to further explore this research direction.